2014
DOI: 10.1111/avsc.12144
|View full text |Cite
|
Sign up to set email alerts
|

Small wetlands are critical for safeguarding rare and threatened plant species

Abstract: Question Rare and threatened species are a common focus of natural area protection, but selecting sites to protect them must be balanced against other conservation objectives. Using a series of wetlands as a case study, we ask: (i) will protecting sites based on species rarity capture all critical community types; (ii) do rare plant species occur in rare environments; and (iii) will safeguarding large wetlands protect taxonomic and functional richness of rare and threatened species? Location Southern New Zeala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 57 publications
1
31
0
1
Order By: Relevance
“…In fact, many studies have found little or no relationship between the degree of nestedness and SLOSS (Berglund & Jonsson, ; Cook, ; Cutler, ; McLain & Pratt, ; Peintinger, Bergamini, & Schmid, ; Simberloff & Martin, ). In addition, it appears that most systems are either not nested or only weakly nested by patch size (Acosta & Robertson, ; Dauber, Bengtsson, & Lenoir, ; Hokkanen, Kouki, & Komonen, ; Mohd‐Azlan & Lawes, ; Richardson et al, ; Rosch et al, ). This might be because species occurrence is not only affected by extinction, but is also affected by colonization (see Section ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, many studies have found little or no relationship between the degree of nestedness and SLOSS (Berglund & Jonsson, ; Cook, ; Cutler, ; McLain & Pratt, ; Peintinger, Bergamini, & Schmid, ; Simberloff & Martin, ). In addition, it appears that most systems are either not nested or only weakly nested by patch size (Acosta & Robertson, ; Dauber, Bengtsson, & Lenoir, ; Hokkanen, Kouki, & Komonen, ; Mohd‐Azlan & Lawes, ; Richardson et al, ; Rosch et al, ). This might be because species occurrence is not only affected by extinction, but is also affected by colonization (see Section ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, if sets of many small patches are more heterogeneous than sets of few large patches then we might find SS > SL. In fact this was the most common explanation provided by authors for their findings of SS > SL in my review of empirical SLOSS studies (Baz & Garcia Boyero, 1996;Dauber et al, 2006;Dzwonko & Loster, 1989;Game & Peterken, 1984;Magura, Ködöböcz, & Tόthmérész, 2001;Martínez-Sanz, Cenzano, Fernández-Aláez, & García-Criado, 2012;McNeil & Fairweather, 1993;Peintinger et al, 2003;Richardson et al, 2015;Saetersdahl, 1994;Seibold et al, 2017;Simberloff & Gotelli, 1984;Tscharntke, Steffan-Dewenter, Kruess, & Thies, 2002;Virolainen, Suomi, Suhonen, & Kuitunen, 1998).…”
Section: Habitat Heterogeneity Environmental Clumping Patchy Specmentioning
confidence: 90%
“…Other factors alter SOC stocks in the PPR that were not addressed here (Johnson et al, 2005; Johnston, 2014). Headwater wetlands were small and often geographically isolated (Tiner, 2003), so excavation could damage ecosystems critical for safeguarding rare and threatened species (Richardson et al, 2015). Results of this study point to the importance of evaluating PPR wetland SOC, SOC turnover, and restoration in a watershed context.…”
Section: Discussionmentioning
confidence: 99%
“…Sequential deletion of drying wetlands truncates the end of the moisture gradient and causes what is known in fisheries science as a shifting baseline which undermines the ability to detect change. Furthermore, small wetlands are critical for conservation of rare plant species (Richardson et al 2014). Failure to monitor small and/or desiccating wetlands will undermine the ability to detect changes in rare plant biodiversity.…”
Section: Inadequate Monitoring Of Plant Species and Vegetationmentioning
confidence: 99%